2022
DOI: 10.7759/cureus.31297
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of RIPASA and Lintula Scores in Diagnosing Acute Appendicitis Using Surgical Findings as the Gold Standard

Abstract: Background: Appendicitis is an inflammation of the vermiform appendix's inner lining that spreads to its other sections. Appendectomy is still the standard way to cure appendicitis. The diagnosis of acute appendicitis is still clinical and supported by a raised neutrophilic count and imaging studies; moreover, scoring systems, such as the Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) and Lintula scores, help the clinicians in the diagnosis. The main objective of this study was to establish the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…2.6% and this was greatly different from Naem et al who reported a mean RIPASA score of 7.721±3.23. However, the current reported score was close to the Score reported by Mousa et al-who reported a mean score of 9.70 ± 2.12 and this variability can be explained by the different cut off values for diagnostic accuracy and subsequent enrollment of patients with mild cases of query appendicitis [12,14].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2.6% and this was greatly different from Naem et al who reported a mean RIPASA score of 7.721±3.23. However, the current reported score was close to the Score reported by Mousa et al-who reported a mean score of 9.70 ± 2.12 and this variability can be explained by the different cut off values for diagnostic accuracy and subsequent enrollment of patients with mild cases of query appendicitis [12,14].…”
Section: Discussionsupporting
confidence: 81%
“…In the current study-taking into consideration a cut off value of 7.5 for the diagnosis of acute appendicitis-90.15% of cases confirmed acute appendicitis by histopathology, matching the results of Verma et al-who used the same cut off value. But this was higher than the confirmed cases of AA by Naeem et alwho reported only 46.5 % showed +ve histopathological findings of AA and this simply can be explained by inclusion of cases with mild iliac fossa pain in their study [14].…”
Section: Discussioncontrasting
confidence: 57%